2018
DOI: 10.1016/j.cmi.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Staphylococcus aureus phenotype and genotype on the clinical characteristics and outcome of infective endocarditis. A multicentre, longitudinal, prospective, observational study

Abstract: This is the first prospective study to assess the impact of S. aureus phenotype and genotype. Phenotype and genotype provided no additional predictive value beyond conventional clinical characteristics. No evidence was found to justify therapeutic decisions based on vancomycin MIC for either methicillin-resistant or methicillin-susceptible S. aureus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…After initial studies described worse outcomes for methicillin-resistant strains with high vancomycin MIC values [9,30], various metaanalyses on the relevance of MIC in SA infections have associated values ≥2 μg/mL with higher mortality (OR 1.72; 95% CI: 1.34-2.21) and values ≥1.5 μg/mL with [31] and even in IE [32] and bacteremia due to MSSA with MIC ≥1.5 μg/ mL, which was associated with a higher risk of complicated bacteremia [33,34]. In contrast, a longitudinal, prospective, multicenter study of MRSA endocarditis found no association of vancomycin MIC ≥1.5 μg/mL with higher mortality, although it was related to a greater persistence of bacteremia and a higher frequency of sepsis/septic shock, peripheral embolism, and arthritis/osteomyelitis [35]. Likewise, a study on beta-lactamtreated left-sided MSSA endocarditis found no relationship between vancomycin MIC and mortality or microorganism virulence [36].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…After initial studies described worse outcomes for methicillin-resistant strains with high vancomycin MIC values [9,30], various metaanalyses on the relevance of MIC in SA infections have associated values ≥2 μg/mL with higher mortality (OR 1.72; 95% CI: 1.34-2.21) and values ≥1.5 μg/mL with [31] and even in IE [32] and bacteremia due to MSSA with MIC ≥1.5 μg/ mL, which was associated with a higher risk of complicated bacteremia [33,34]. In contrast, a longitudinal, prospective, multicenter study of MRSA endocarditis found no association of vancomycin MIC ≥1.5 μg/mL with higher mortality, although it was related to a greater persistence of bacteremia and a higher frequency of sepsis/septic shock, peripheral embolism, and arthritis/osteomyelitis [35]. Likewise, a study on beta-lactamtreated left-sided MSSA endocarditis found no relationship between vancomycin MIC and mortality or microorganism virulence [36].…”
Section: Discussionmentioning
confidence: 85%
“…Active neoplasm, sepsis/shock, and decade of endocarditis onset (1985-1999 or 2000-2009 vs. 2010-2017) emerged as poor prognostic factors, but early surgery (within first 2 weeks) did not appear to influence the prognosis. A recent multicenter, longitudinal, observational study of SA IE (n = 213 cases) reported a mortality rate of 37% and identified a high Charlson index, congestive heart failure, CNS involvement, and sepsis/septic shock as risk factors [35].…”
Section: Discussionmentioning
confidence: 99%
“…To date, many studies have analysed the association between agr dysfunction and poor clinical outcomes of invasive S. aureus infection in various clinical settings 30,32,43,44,49,50 . Since Schweizer et al reported that SAB with dysfunctional agr was associated with excessive mortality among severely ill patients 29 , subsequent studies have demonstrated that agr dysfunction was associated with higher mortality 31,32 , and the persistence of bacteraemia www.nature.com/scientificreports/ in patients with SAB, especially in MRSA bacteraemia 7,30 .…”
Section: Discussionmentioning
confidence: 99%
“…These strains were obtained from different sources in hospitals geographically distant from each other spread across the territory of Spain (Table 1 ). Specifically, these strains were identified in 10 different collections: six were single-center studies developed at the Hospital 12 de Octubre in Madrid, and the remaining four corresponded to multi-center studies developed at various Spanish hospitals (Muñoz-Gallego et al, 2017 ; San-Juan et al, 2017 ; Fernández-Hidalgo et al, 2018 ). The main focus and objective of the studies for which these strains were collected was source of staphylococcal bacteremia, mainly endocarditis ( N = 214), catheter-related bacteremia (CRB) ( N = 212), skin and soft tissue infections (SSTI) ( N = 66), and bone and joint infections ( N = 100).…”
Section: Methodsmentioning
confidence: 99%